Variables associated with physical fighting among US high-school students - Rudatsikira, Emmanuel (BioMed Central, 2008)
BACKGROUND: Violence among adolescents is an important public health problem in the United States. This study was conducted to estimate the prevalence of having been engaged in physical fighting on school property and associated factors of the behavior among school-going adolescents in the United States. METHODS: This study was based on secondary analysis of the United States Youth Risk Behavior Survey (YRBS) conducted in 2005. The sampling frame included all private and public school in the country, stratified by region and urbanicity based on the US census bureau data. Frequencies and proportions were obtained for the outcome and explanatory variables. Logistic regression analysis was used to estimate the level of association between explanatory variables and the outcome (having been involved in a physical fight). RESULTS: Of the 13,857 respondents, 13.5% (18.2% for males and 8.8% for females) reported physical fighting onschool property in the last 12 months to the survey. Males were more likely to have been in a physical fight than females (OR = 2.23; 95% CI [1.89, 2.63]). Respondents aged 17 years or older were less likely to report physical fighting than those who were 14 years or younger. Compared to Whites, American Indians or Alaska Natives, Blacks, Native Hawaii or other Pacific Islanders, and Hispanics were more likely to report physical fighting on school property (OR = 2.11; 95% CI [1.22, 3.66], OR = 1.72; 95% CI [1.42, 2.0], OR = 2.18; 95% CI [1.01, 4.79], and OR = 1.74; 95% CI [1.41, 2.16] respectively). Physical fighting on school property was also positively associated with cigarette smoking (OR = 1.70; 95% CI [1.37, 2.10]), drinking alcohol (OR = 1.45; 95% CI [1.20, 1.76]), use of illegal drugs (OR = 1.73; 95% CI [1.42, 2.12]), having had property stolen or deliberately damaged on school property (OR = 2.06; 95% CI [1.74, 2.44]), having been threatened or injured with a weapon on school property (OR = 2.63; 95% CI [2.06, 3.34]), and playing videogame three or more hours a day (OR = 1.29; 95% CI [1.07, 1.56]). CONCLUSION: These findings suggest that physical fighting among US High School students is widespread and positively associated with victimization (having been threatened or injured with a weapon on school property) and other risky behaviors such as smoking, alcohol and drugs use. Intervention programs to prevent/control those risky behaviors as well as further attention on the association between physical fighting and victimization at school through longitudinal research are warranted.